2015
DOI: 10.1371/journal.pone.0139302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Multi-Dimensional and Inter-Sectoral Intervention on the Adherence of Psychiatric Patients

Abstract: BackgroundIn psychiatry, hospital stays and transitions to the ambulatory sector are susceptible to major changes in drug therapy that lead to complex medication regimens and common non-adherence among psychiatric patients. A multi-dimensional and inter-sectoral intervention is hypothesized to improve the adherence of psychiatric patients to their pharmacotherapy.Methods269 patients from a German university hospital were included in a prospective, open, clinical trial with consecutive control and intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…In addition, interventions for healthcare professionals could involve repetitive feedbacks and were often dependent on the contents of the intervention in terms of how these professionals received such feedbacks [ 23 , 24 ]. Unlike other studies conducted, interventions on medication simplification by changing direct services delivered by healthcare professionals [ 25 , 26 , 27 , 28 ], we believe that the significance of our study was in its approach to provide a system change. As Schneider et al described, over 95% of health institutions in the United States use the CPOE system [ 29 ]; therefore, our study demonstrating our collaborative approach toward changing the HIS can be instrumental in enhancing this system’s feasibility, serve as a potentially adaptable method to enhance the CPOE system in other healthcare settings, and prove to be a methodological tool for real-world-based intervention studies.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, interventions for healthcare professionals could involve repetitive feedbacks and were often dependent on the contents of the intervention in terms of how these professionals received such feedbacks [ 23 , 24 ]. Unlike other studies conducted, interventions on medication simplification by changing direct services delivered by healthcare professionals [ 25 , 26 , 27 , 28 ], we believe that the significance of our study was in its approach to provide a system change. As Schneider et al described, over 95% of health institutions in the United States use the CPOE system [ 29 ]; therefore, our study demonstrating our collaborative approach toward changing the HIS can be instrumental in enhancing this system’s feasibility, serve as a potentially adaptable method to enhance the CPOE system in other healthcare settings, and prove to be a methodological tool for real-world-based intervention studies.…”
Section: Discussionmentioning
confidence: 93%
“…7,23,24 The remaining five studies (29%) included patients with different conditions such as venous thromboembolism (VTE), psychiatric disorder, glaucoma, kidney transplant and residents of aged care facilities. 10,13,14,25,26 Almost all the studies reported direct measures of adherence except three studies that reported the potential improvement of adherence as a result of decreasing treatment burden, 23 increase medication exposure, 24 and reduce the time of medication administration. 26 Thirteen of the seventeen studies reported clinical outcomes associated with the simplification of drug regimen, while four studies reported adherence measures with no clinical outcomes.…”
Section: Dovepressmentioning
confidence: 99%
“…9 Furthermore, frequent hospitalizations lead to changes in the drug therapy regimen, particularly post-hospital discharge, which at times becomes more complex due to the initiation of newly prescribed medicines. 10 Furthermore, an Italian study that assessed the association of regimen complexity with the risk of medication non-adherence suggested that regimen complexity had an independent association with the relative non-adherence risk. 11 Consequently, it has been reported that the interventions to reduce regimen complexity are sought to have a potential impact on the level of medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…It is a generic tool, which can be administered regardless of the disease and the prescribed drug. It has been validated so far in different clinical settings, namely statin therapy [15], rheumatoid arthritis [16], asthma [17], psychosis [18], and has been used for assessing adherence in many clinical studies worldwide [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%